2020
DOI: 10.3390/polym12112561
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Experimental Evaluation of Agarose-Based Semi-Interpenetrating Polymer Network Hydrogels as Materials with Tunable Rheological and Transport Performance

Abstract: This study introduces an original concept in the development of hydrogel materials for controlled release of charged organic compounds based on semi-interpenetrating polymer networks composed by an inert gel-forming polymer component and interpenetrating linear polyelectrolyte with specific binding affinity towards the carried active compound. As it is experimentally illustrated on the prototype hydrogels prepared from agarose interpenetrated by poly(styrene sulfonate) (PSS) and alginate (ALG), respectively, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 87 publications
2
12
0
Order By: Relevance
“…Hydrogels with distinct gelation mechanisms (physical, ionic, chemical crosslinking) [ 20 ] were studied. As an example of a physically crosslinked matrix, the linear thermoreversible polysaccharide agarose (Agarose E, Condalab, Madrid, Spain) at 1 wt.%, was used [ 21 ]. As an example of an ionically crosslinked matrix, sodium alginate (Sigma-Aldrich, Prague, Czech Republic) at 2 wt.% crosslinked by calcium chloride (Lach-Ner, Neratovice, Czech Republic) at a two to one weight ratio was chosen [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogels with distinct gelation mechanisms (physical, ionic, chemical crosslinking) [ 20 ] were studied. As an example of a physically crosslinked matrix, the linear thermoreversible polysaccharide agarose (Agarose E, Condalab, Madrid, Spain) at 1 wt.%, was used [ 21 ]. As an example of an ionically crosslinked matrix, sodium alginate (Sigma-Aldrich, Prague, Czech Republic) at 2 wt.% crosslinked by calcium chloride (Lach-Ner, Neratovice, Czech Republic) at a two to one weight ratio was chosen [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The materials and their concentrations and ratios were selected on the basis of data previously reported [ 20 , 21 , 22 , 23 , 24 ] and can be seen in the table below ( Table 10 ).…”
Section: Methodsmentioning
confidence: 99%
“…While a variety of methods including dynamic and static light scattering, , X-ray scattering, , turbidity/cloud point measurements, , and advanced electron microscopy methods have been used for investigating the internal morphology of hydrogels, small-angle neutron scattering (SANS) is particularly useful given that both the pore size and the dimensions of typical gel inhomogeneities lie in the accessible SANS length scale (1–200 nm). SANS is particularly useful for characterizing nanoparticle network hydrogels given that the mesh size of the nano/microgel, the mesh size between the nano/microgels, and the absolute size of the nano/microgels used all lie within the accessible SANS length scale (unlike with other methods) . SANS studies on preformed nano/microgel network hydrogels at an equilibrium swelling state have been reported both by our group and others. Specific to SNPs and soluble starch, our previous SANS results suggested that SS hydrogels have significantly lower Porod exponents (corresponding to more Gaussian, swollen chains), significantly higher fluid correlation lengths (indicating larger gel mesh sizes), and much larger Lorentzian scales (indicating a significantly more fluid network structure) than SNP-based hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of hydrogels must vary according to the specific needs of individual applications, e.g., for drug delivery systems, suitable transport properties are crucial to their application. Recent studies [1][2][3][4] have focused on various strategies to improve these properties in hydrogels using a process such as the use of interpenetrating networks, composite structures, and dual crosslinking. Overall, hydrogel preparation methods that simultaneously mimic the hydration, strength, and stiffness of soft and supporting tissues have the potential to be used in a much wider range of biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, hydrogel preparation methods that simultaneously mimic the hydration, strength, and stiffness of soft and supporting tissues have the potential to be used in a much wider range of biomedical applications. Using semi-interpenetrating polymer networks (semi-IPN) is a suitable way to modify the material properties by manipulation of the internal chemical and morphological architecture [2][3][4].…”
Section: Introductionmentioning
confidence: 99%